The price impact of lending relationships - Ingrid Stein (Deutsche Bundesbank, 2011)
This study analyzes the impact of bank relationships on a firm's cost of debt. We focus on relationships with the main bank. We find that a firm's cost of debt decreases with relationship strength, proxied by the share of bank debt provided by the main lender, but rises with relationship length. While the increase over time is weak on average, bank-dependent borrowers face a significant premium after several relationship years. Moreover, cost of debt increases with concentration in the lender's portfolio. Switching the main lender initially leads to only a small price discount on average. However, the discount is considerable for borrowers that switch and had a strong relationship to the previous main lender. Our results indicate that the information advantage acquired by the relationship bank leads to benefits for the firm, but also to potential hold-up costs in the long-term. Moreover, additional costs may result from concentration risks faced by the lender, inducing borrowers to switch to larger relationship banks.
Keywords: G21; G32; 330; Lending relationship; SME; German banking system